Wave run-up on sandbag slopes - Thamnoon Rasmeemasmuang (Maejo International Journal of Science and Technology, 2014)
On occasions, sandbag revetments are temporarily applied to armour sandy beaches from erosion. Nevertheless, an empirical formula to determine the wave run -up height on sandbag slopes has not been available heretofore. In this study a wave run-up formula which considers the roughness of slope surfaces is proposed for the case of sandbag slopes. A series of laboratory experiments on the wave run -up on smooth slopes and sandbag slopes were conducted in a regular-wave flume, leading to the finding of empirical parameters for the formula. The proposed empirical formula is applicable to wave steepness ranging from 0.01 to 0.14 and to the thickness of placed sandbags relative to the wave height ranging from 0.17 to 3.0. The study shows that the wave run-up height computed by the formula for the sandbag slopes is 26-40% lower than that computed by the formula for the smooth slopes.